2001
DOI: 10.1051/fruits:2001104
|View full text |Cite
|
Sign up to set email alerts
|

Régénération directein vitrode l'Ananas comosus (L.) Merril var. Cayenne à partir de couronnes cultivées en milieu liquide

Abstract: Introduction. The majority of work on the in vitro multiplication of pineapple has used explants of various origins, but far fewer has used crowns for obtaining in vitro plantlets. In addition, the plant regeneration carried out through the formation of calli can induce somaclonal variations. So an in vitro method of direct regeneration from the crowns was tested. Materials and methods. After disinfection, pineapple crowns of the Cayenne variety were cultivated on a liquid medium of Murashige and Skoog half-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Moreover, the optimum concentration of BAP was not yet recommended extensively. BAP at the concentration of 1.0 (3), 2.0 (11,12), 2.5 (13,14), 3.0 (4) and 4.0 mg/l (15) were recommended for the multiplication of plantlet. It was (14) stated that the use of a wider concentration range in caster beans increased the castor proliferation rate five times higher.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the optimum concentration of BAP was not yet recommended extensively. BAP at the concentration of 1.0 (3), 2.0 (11,12), 2.5 (13,14), 3.0 (4) and 4.0 mg/l (15) were recommended for the multiplication of plantlet. It was (14) stated that the use of a wider concentration range in caster beans increased the castor proliferation rate five times higher.…”
Section: Introductionmentioning
confidence: 99%
“…Firoozabady and Gutterson (2003) reported a cyclic procedure of 15 days long multiplication while Fernando (1986) transferred the shoots to fresh medium each 21 days. Incubation for 30 (Gonzales et al, 2005;Firoozabady and Gutterson, 2003;Almeida et al, 2002;Soneji et al, 2002 a;Singh and Manual, 2000;Devi et al, 1997;Dewald et al, 1988;Bordoloi and Sarma, 1993;Kofi and Adachi, 1993;Fitchet, 1990;Zepeda and Sagawa, 1981), 35 (Khatun et al, 1997), 42 (Perez et al, 2009;Khan et al, 2004;Sripaoraya et al, 2003;Bhatia and Ashwath, 2002;Rahman et al, 2001;Teng, 1997;Aydieh et al, 2000;Escalona et al, 1999), 50 ( Mathew and Rangan, 1981;Mathew et al, 1979), 60 (Hamad and Taha, 2008;Gangopadhaya et al, 2005;Be and Debergh, 2006;Hirimburgama and Wijesinghe, 1992;Mathew and Rangan, 1976), 64 (Omokoio et al, 2001), 70 (Soneji et al, 2002 b), 75 (Teixeira et al, 2006), 84 (Mhatre and Rao, 2002) and 112 days (Nelson, et al, 2015) were reported. Cytokinin particularly BAP was recommended singly (Nelson, et al, 2015: Akin-Idowu, et al, 2014: Zuraida, et al, 2011: Hamad and Taha, 2008Be and Debergh, 2003;…”
Section: Introductionmentioning
confidence: 99%
“…Or, les explants utilisés chez Ananas comosus var. comosus et ayant donnés les meilleurs résultats sont les bourgeons axillaires de feuilles de couronnes d'ananas (Omokolo et al, 2001 ;Zuraida et al, 2011 ;Ibrahim et al, 2013 ;Usman et al, 2013). A notre connaissance, aucune étude n'a encore évalué l'influence de l'âge des bourgeons sur le comportement in vitro de ces bourgeons chez l'ananas.…”
Section: Introductionunclassified